Dan Shen, Style and Rhetoric of Short Narrative Fiction: Covert Progressions Behind Overt Plots (ENTHYMEMA, 2014)
Si recensisce Shen, Dan. Style and Rhetoric of Short Narrative Fiction: Covert Progressions Behind Overt Plots. New York and London: Routledge. 2014. Stampa.